2013
DOI: 10.1371/journal.pone.0081058
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Zostera marina and Cymodocea nodosa to Light-Limitation Stress

Abstract: The effects of light-limitation stress were investigated in natural stands of the seagrasses Zostera marina and Cymodocea nodosa in Ria Formosa coastal lagoon, southern Portugal. Three levels of light attenuation were imposed for 3 weeks in two adjacent meadows (2–3 m depth), each dominated by one species. The response of photosynthesis to light was determined with oxygen electrodes. Chlorophylls and carotenoids were determined by high-pressure liquid chromatography (HPLC). Soluble protein, carbohydrates, malo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
71
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 51 publications
9
71
0
Order By: Relevance
“…Total phenol content is considered a suitable indicator of the ecophysiological status of seagrasses (Migliore et al, 2007; Rotini et al, 2013), since seagrasses are known to modulate their phenol content in response to stressful environmental conditions (e.g., Rotini et al, 2011; Darnell and Heck, 2013; Silva et al, 2013; Arnold et al, 2014). The reduced phenol concentrations at 28 m may be related to a simultaneous reduction in the phenolic biosynthesis and increase of phenolic mobilization, both triggered by low light regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Total phenol content is considered a suitable indicator of the ecophysiological status of seagrasses (Migliore et al, 2007; Rotini et al, 2013), since seagrasses are known to modulate their phenol content in response to stressful environmental conditions (e.g., Rotini et al, 2011; Darnell and Heck, 2013; Silva et al, 2013; Arnold et al, 2014). The reduced phenol concentrations at 28 m may be related to a simultaneous reduction in the phenolic biosynthesis and increase of phenolic mobilization, both triggered by low light regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Acclimation and adaptation to light gradients occur in seagrasses through a multilevel strategy, which includes changes in (i) meadow structure (Collier et al, , 2009Olesen et al, 2002;Peralta et al, 2002), (ii) shoot morphology (Dalla Via et al, 1998;Longstaff and Dennison, 1999;Oliv e et al, 2013), (iii) leaf-surface features (Enriquez et al, 1992;Durako, 2007), (iv) pigment and protein content (Casazza and Mazzella, 2002;Collier et al, 2008;Mazzuca et al, 2009;Pirc, 1986;Sharon et al, 2009;Silva et al, 2013); (v) ratio between photosystem I and II units (Dattolo et al, 2013;Sharon et al, 2011) and (vi) photosynthetic parameters, such as photosynthetic efficiency (a), maximum electron transport rate (ETR max ), and saturating irradiance (E k ) (Campbell et al, 2003;Collier et al, 2009;Larkum et al, 2006;Silva and Santos, 2003). In addition to these responses, seagrasses can alter resource allocation patterns to optimize carbon balance (Alcoverro et al, 2001), and can adapt their reproductive cycle along the bathymetric cline, as observed in Mediterranean species (Buia and Mazzella, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Under decreased irradiances (e.g. at 20 in comparison with 5 m depth), this seagrass shows increased photochemical energy conversion efficiency (α); this is a common strategy of marine angiosperms when they are subjected to chronic light deprivation (Collier et al 2012), including C. nodosa (Silva et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly pertinent under scenarios of global change, in which the intensity and frequency of anthropogenic perturbations are increasing. For example, increasing turbidity in coastal areas alters the dominance and functioning of seascapes dominated by submersed vegetation, particularly those constituted by marine angiosperms (seagrasses) (Duarte et al 2008, Silva et al 2013. Understanding the physiological response of seagrasses and accompanying seaweeds to altered light regimes is therefore important (Collier et al 2012).…”
Section: Introductionmentioning
confidence: 99%